ENERGY AND CARBON MANAGEMENT SYSTEMS TO REDUCE GHG EMISSIONS IN THE OIL & GAS INDUSTRY: STANDARDS APPLICATIONS FOR FPSO VESSELS DECARBONIZATION - Silva, Gustavo Castro Ribeiro Ferreira (2024)
This research investigates energy and carbon management systems applied to the Oil and Gas (O&G) industry in its quest for carbon reduction in Exploration and Production (E&P) operations. It focuses on enhancing energy efficiency and reducing Greenhouse Gas (GHG) emissions, specifically through a case study of Floating Production, Storage, and Offloading (FPSO) vessels used in offshore O&G production in ultra-deep waters. The thesis centers on the main offshore production technology employed in Brazil and other regions with ultra-deep water fields. The primary contribution of this research is the development of guidelines for decarbonizing the topside operations of FPSOs. Addressing the pressing issue of reducing the carbon content of produced O&G, this research provides original approaches and solutions for the industry. The originality of the thesis lies in its adaptation of energy and carbon management standardization systems to FPSO operations. The findings offer valuable insights and guidance for top management, stakeholders, and shareholders, aiming to integrate sustainable development practices into O&G production operations. By implementing these energy and carbon management actions, the thesis demonstrates how more efficient operations can result in lower fuel consumption and significant reductions in GHG emissions, particularly carbon dioxide (CO2). The thesis also presents improved energy efficiency and operational performance indicators, designed to assess, demonstrate, and report on these enhancements. It provides practical steps and detailed guidance for conceiving and implementing the proposed management systems, specifically tailored to FPSO operations. This case study not only contributes to innovation in sustainable performance management but also offers a practical tool for FPSO operators striving for carbon neutrality in offshore operations, aligning with global efforts to mitigate GHG emissions. The thesis underscores the importance of energy and carbon management systems as a crucial strategy for achieving carbon neutrality and sustainable development in the O&G sector.